2006
DOI: 10.1016/j.mod.2006.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila CK2 regulates lateral-inhibition during eye and bristle development

Abstract: Lateral inhibition is critical for cell fate determination and involves the functions of Notch (N) and its effectors, the Enhancer of Split Complex, E(spl)C repressors. Although E(spl) proteins mediate the repressive effects of N in diverse contexts, the role of phosphorylation was unclear. The studies we describe implicate a common role for the highly conserved Ser/Thr protein kinase CK2 during eye and bristle development. Compromising the functions of the catalytic (alpha) subunit of CK2 elicits a rough eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(83 citation statements)
references
References 87 publications
8
75
0
Order By: Relevance
“…AmunTRFP (red) localizes to nuclei (B), as indicated by the DNA dye Vybrant Green (B9). antennal-eye imaginal disc; Bose et al 2006), we observe a reduction in eye size (see Figure S3) consistent with a role for Amun in eye development (see above). Reduction of Amun levels under control of the sca-Gal4 or ptc-Gal4 driver results in multiple bristle defects including missing, supernumerary, and misplaced macrochaetae, as well as probable shaft-to-socket transformations ( Figure 6, E and F, respectively).…”
Section: ; Muller Et Al 2005) Ep(x)1503 a Uas-containing Transsupporting
confidence: 82%
See 1 more Smart Citation
“…AmunTRFP (red) localizes to nuclei (B), as indicated by the DNA dye Vybrant Green (B9). antennal-eye imaginal disc; Bose et al 2006), we observe a reduction in eye size (see Figure S3) consistent with a role for Amun in eye development (see above). Reduction of Amun levels under control of the sca-Gal4 or ptc-Gal4 driver results in multiple bristle defects including missing, supernumerary, and misplaced macrochaetae, as well as probable shaft-to-socket transformations ( Figure 6, E and F, respectively).…”
Section: ; Muller Et Al 2005) Ep(x)1503 a Uas-containing Transsupporting
confidence: 82%
“…The following strains were used for the study of CG2446 (Amun): eyeless (ey)-Gal4 (Bose et al 2006) (Bloomington Drosophila Stock Center); decapentaplegic (dpp)-Gal4/TM6B (StaehlingHampton et al 1994); pannier (pnr)-Gal4/TM3 (Heitzler et al 1996), a gift from Gines Morata, Centro de Biología Molecular Severo Ochoa (Madrid); patched (ptc)-Gal4 (Speicher et al 1994) (Bloomington Drosophila Stock Center); scabrous (sca)-Gal4/CyO (Mlodzik et al 1990), a gift from Andrea Brand, University of Cambridge (Cambridge, UK); UAS-myr-mRFP/ TM6B (Bloomington Drosophila Stock Center); stripe MD710 (sr)-Gal4/TM6B (Calleja et al 2002;Usui et al 2004), a gift from Pat Simpson, University of Cambridge (Cambridge, UK); UASAmunRNAi and UAS-Dicer2 (Dietzl et al 2007), obtained from the Vienna Drosophila RNAi Center; and P[lArB]A101.IF3 (neur A101 -LacZ)/TM3 (Bellen et al 1989), a gift of Hugo Bellen, Baylor College of Medicine (Houston).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently found that loss of the MC's elicited by ectopically expressed wild type M8 is strongly rescued by coexpression of a UAS-CK2a-RNAi construct or UAS-Tik, a CK2-DN (Bose et al, 2006;Kahali et al, 2009). These results suggested that phosphorylation also regulates antagonism of ASC by M8 during SOP selection (Fig.…”
Section: M8-ctd More Strongly Suppresses the Bristle Defects Of Ectopmentioning
confidence: 83%
“…Moreover, suppression by M8-CtD is unlikely to involve competition for, or sequestration of, endogenous CK2. The interaction of CK2 with M8 or M8-CtD is disrupted upon phosphorylation (Kahali and Bidwai, unpublished;Karandikar et al, 2004), and while halved CK2 dosage is sufficient for proper N signaling, its further knockdown leads to supernumerary (''twinned'') SOP's/R8's, and to rough eyes due to impaired lateral inhibition (Bose et al, 2006). Consistent with the possibility that (endogenous) CK2 levels are not rate limiting for lateral inhibition, the reduced eye of M8SD is not suppressed by decreased CK2 levels or E(spl)-dosage (Kahali, unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation